THE “EXTRA-MEDIA” THICKNESS OF CAROTID ARTERIES AS A NOVEL MARKER OF PERIVASCULAR VISCERAL ADIPOUS TISSUE: ACCENT ON THE RELATION WITH VASCULAR REMODELLING PARAMETERS - M. A. Druzhilov; Yu. E. Beteleva; I. V. Khein; T. Yu. Kuznetsova (Российский кардиологический журнал, 2016)
Aim. To perform ultrasound assessment of the “extra-media” thickness (EMT) of carotid arteries and to analyze its association with vascular stiffness and sonographical indexes of carotid arteries condition in patients with abdominal obesity.Material and methods. Totally, 84 normotensive men assessed, non-sympthomatic by cardiovascular diseases and with non high risk by SCORE (mean age 44,7±4,2 y.) with abdominal obesity. We performed triplex scanning of brachiocephalic arteries with measurement of carotid EMT, echocardiographical measurement of epicardial fat and ultrasound assessment of abdominal visceral fat tissue; bifunctional 24-hour monitoring of blood pressure.Results. Carotid EMT was from 0,3 mm to 0,8 mm (mean 0,43±0,12 mm). Linear correlation coefficient of the parameter was 0,49 for the age (p<0,001), for body mass index 0,47 (p<0,001), for waist circumference 0,32 (p<0,01), for epicardial fat 0,71 (p<0,001), for abdominal visceral fat 0,48 (p<0,001), for fasting glucose 0,35 (p<0,001), for high-sensitive C-reactive protein of blood 0,42 (p<0,001), for carotid intima-media 0,41 (p<0,001), for aortic pulse wave velocity 0,56 (p<0,001). Significantly higher EMT of carotid arteries were found in patients with carotid atherosclerosis (0,63±0,08 mm vs 0,39±0,08 mm, р<0,001), increase of carotid “intima-media” thickness (0,49±0,12 mm vs 0,41±0,12 mm, р<0,01) and high levels of pulse wave velocity in aorta (0,51±0,12 mm vs 0,38±0,10 mm, р<0,001).Conclusion. The EMT correlation revealed, for carotid arteries with the age, indirect and direct markers of visceral obesity, metabolic risk factors, vascular remodeling parameters. Carotid atherosclerosis patients, with intima-media hypertrophy, increased vessel stiffness had higher levels of this perivascular visceral fat tissue marker.